Warfarin-Induced Skin Necrosis in the Presence of Acute Hepatic Injury and May-Thurner Syndrome. (April 2019) - Tilton, Carrie; Livengood, Spencer; Hodges, Jeremy; Marshall, Jessica
Purpose: The purpose of the report is to describe a patient with warfarin-induced skin necrosis in the presence of acute hepatic injury and significant risk factors for venous thromboembolism, including protein C deficiency and May-Thurner syndrome.Summary: A 44-year-old female with multiple comorbidities presented to the emergency department with a significantly elevated international normalized ratio (INR > 15.9) rapidly reversed with vitamin K and fresh frozen plasma. Due to the findings of bilateral acute on chronic deep vein thromboses (DVTs) and suspected warfarin-induced skin necrosis, a heparin infusion was initiated but later discontinued due to endogenous partial thromboplastin times (PTT) elevations despite dose reductions. Although the necrosis encompassed large areas of the fatty tissue, the depth of necrosis remained mostly superficial. Supportive care and wound management were provided following warfarin reversal; no skin grafts or amputations were performed.Conclusion: A 44-year-old female developed a complicated probable warfarin-induced skin necrosis in the setting of acute liver failure, septic shock, May-Thurner syndrome, previously failed anticoagulation, and acute deep vein thrombosis.